Relationship between power strength and anaerobic power index as a clear picture of the effect of strength training among young soccer elite players - Mohammed Zerf; Mohamed Arab. Kerroum; Bouabdellah S.B.A (Kharkiv State Academy of Physical Culture, 2019)
Purpose: muscle contraction has both mechanical to produce movement and metabolic properties to produce energy. However, manipulation of strength training planes (horizontal or vertical) subject to be an important training strategy to develop soccer-specific power-based actions. Depending on mode of exercise and more important the energy demands. Material & Methods: this cross-sectional study was conducted to inspect the relation between power strength and anaerobic power index, proper to mode of exercise (vertical vs horizontal) among young soccer elite players. To achieve this goal, we based on anaerobic capacity repeat sprint test power index for103 male players with mean age (18.55±0.48) years, involved in the Oran league competition division one. In addition to their strength in Vertical Jump (VJ) and Standing Long Jump Test (SLJ), conducted in the Omni sports complex of the institute physical education and sport Chlef. Results: significant inverse correlations record between power strength and anaerobic power index in all comparisons practised. Support by the index of Max power anaerobic and fatigue as super predictors of players performance in horizontal plane. The opposite of vertical plane where the index of fatigue and Min power anaerobic are the super predictors. Conclusions: our results confirmed that to have a clear picture of the effect of strength training on physical performance. Trainers must take in their consideration, the mode of exercise and their energy index power demands affirmed in present via the development of max power anaerobic to enhance not only minimal but also the index of fatigue requiring the good developments of neuromuscular function, in which max power anaerobic levels play a big part in maximizing scores not only in vertical plane but also in horizontal jump.